Peutz Jeghers Syndrome - M Purnomo Isnaeni; Marcellus Simadibrata; Murdani Abdullah; Ari Fahrial Syam; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Peutz-Jeghers Syndrome (PJS) is a rare condition that tends to run in families. Diagnosis of PJS is made if a person has polyps in the gastrointestinal (GI) tract and at least two of the following: polyps in the small bowel, melanin spots, and/or a family history of PJS. The typical clinical manifestation of the disease is associated with complications secondary to intestinal polyps often requiring surgical treatment. A young woman, 29 years old with PJS had been hospitalized in Cipto Mangunkusumo hospital. She was suffering from GI complication secondary to her polyps such as abdominal pain, nausea, vomited every time she takes her meal and milk, anorexia, fatigue, weakness, chronic diarrhea with hematoschezia. Upper and lower endoscopy showed the multiple polyps along from esophagus, gaster, duodenum, and her colon. Histopathology examination confirmed the type of polyps is Peutz Jeghers with the unique morphology consisting of mucosa with interdigitating smooth muscle bundles that yield a characteristic branching tree appearance. We also found the family tree of this patient and it is a good evident how PJS can be inherited in a family. Keywords: Peutz-Jeghers syndrome, melanin spots, polypsry